2012
DOI: 10.1089/fpd.2011.1119
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Antibacterial Activity of Tetrandrine AgainstStaphylococcus aureus

Abstract: Tetrandrine (TET) is a bis-benzylisoquinoline alkaloid derived from the radix of Stephania tetrandra S. Moore. TET performs a wide spectrum of biological activities. The radix of S. tetrandrae has been used traditionally in Asia, including Korea, to treat congestive circulatory disorders and inflammatory diseases. The aim of this study was to examine the mechanism of antibacterial activity of tetrandrine against Staphylococcus aureus. The mechanism was investigated by studying the effects of TET in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…It is traditionally used in China and Korea to treat patients with arthritis. Previous studies have shown that it possesses anti-arrhythmic[14], anti-hypertensive[15], cardio-protective[16], anti-tumorigenic[17], and anti-inflammatory effects[18]. We have demonstrated that TET exhibits anti-inflammatory and hepato-protective effects in mice[19], [20], and it inhibits IL-6 and TNF-α production in macrophages.…”
Section: Introductionmentioning
confidence: 83%
“…It is traditionally used in China and Korea to treat patients with arthritis. Previous studies have shown that it possesses anti-arrhythmic[14], anti-hypertensive[15], cardio-protective[16], anti-tumorigenic[17], and anti-inflammatory effects[18]. We have demonstrated that TET exhibits anti-inflammatory and hepato-protective effects in mice[19], [20], and it inhibits IL-6 and TNF-α production in macrophages.…”
Section: Introductionmentioning
confidence: 83%
“…In this study both CTSA and EDTA treatments have been identified to be effective anti– S. aureus biofilm agents when used alone, but this study also showed a lack of synergy in combination, indicating little value in using both treatments together. EDTA has been shown to enhance the action of the antimicrobial activities of other compounds against S. aureus infection and biofilm . This enhancement may be due to the action of EDTA to increase the permeability of bacterial cells, thus allowing an enhanced entrance of these antimicrobials into the bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Northalrugosidine (28) showed the most potent in vitro activity against Leishmania donovani promastigotes (0.28 lM), and the highest selectivity (29.3-fold) versus its general cytotoxicity against HT-29 human colon adenocarcinoma cells (Naman et al 2015). Meanwhile the reduction in parasite burden to the murine spleen and liver after the in vivo testing of northalrugosidine at 2.8, 5.6, and 11.1 mg/kg per animal when administered intravenously supported the idea that it could be further investigated as a potential new drug candidate or lead molecule for drug discovery (Naman et al ,9, 10, 21, 25, 28, 29, 52 Ye and Dyke (1989), Ye et al ( , 2013, Chen et al (2002Chen et al ( , 2003, Chea et al (2010), Baghdikian et al (2013), Fadaeinasab et al (2015), Naman et al (2015) Antibacterial effects 9, 52 Lee et al (2011Lee et al ( , 2012, Avci et al (2018), Yin et al (2015) Antifungal effects 9, 49, 52 Li and Zhang (2006) Anti-inflammatory effects 1, 5, 9, 10, 21, 25, 39, 49 Guo et al (20151, 5, 9, 10, 21, 25, 39, 49 Guo et al ( , 2018 1,9,10,21,25,39,50,52 Bhagya and Chandrashekar (2018) Wong et al (2000), Rao (2002), Huang et al (1999), Li et al (2001Li et al ( , 2003, Zhou et al (2007), Pinelli et al (2010), Shen et al (1999), Young et al (1994), Orallo (2004), Yu et al (1993),…”
Section: Antimicrobial Effectsmentioning
confidence: 95%